2020
DOI: 10.1088/1361-6579/ab9b67
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in pulse risetime measured by multi-site photoplethysmography

Abstract: Objective: It is accepted that changes in the peripheral pulse waveform characteristics occur with ageing. Pulse risetime is one important feature which has clinical value. However, it is unclear how it varies across the full age spectrum from child to senior and for different peripheral measurement sites. The objectives of this study were to determine the association between age and pulse risetime characteristics over an 8-decade age range at the ears, fingers, and toes, and to consider effects arising from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Note that we did not employ any hyperparameter tuning which might further improve our results, but certainly only on a gradual scale. In contrast, other authors who did not explicitly mention a subject-based dataset split reported substantially lower prediction errors [33][34][35]62].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Note that we did not employ any hyperparameter tuning which might further improve our results, but certainly only on a gradual scale. In contrast, other authors who did not explicitly mention a subject-based dataset split reported substantially lower prediction errors [33][34][35]62].…”
Section: Discussionmentioning
confidence: 94%
“…In a practical application, data from new subjects (e.g., from patients admitted to hospital) would lead to a prediction error much closer to the MAE reported on the non-mixed dataset rendering the whole method unsuited for clinical use. The impact of age, comorbidities, medication and measurement equipment have a large influence on PPG morphology [ 34 , 63 ]. These differences can be exploited as features for the non-invasive assessment of cardiovascular aging [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we did not employ any hyperparameter tuning which might further improve our results, but certainly only on a gradual scale. In contrast, other authors who did not explicitly mention a subjectbased dataset split reported substantially lower prediction errors [30,31,32,54]. These differences suggest that morphological inter-individual variations due to age, comorbidities, medication and measurement equipment prevent the investigated NNs to generalize well.…”
Section: Discussionmentioning
confidence: 75%
“…caused by age and cardiovascular diseases, certainly affects the association of the signal shape to a particular BP. The equipment in a hospital setting differs as well and, more importantly, the contact pressure of a PPG sensor can affect the pulse morphology [30,31,32]. Therefore the ability of the learning algorithm to generalize well may be impaired.…”
Section: Introductionmentioning
confidence: 99%